Automatización del registro y control de los procesos de hospedaje, restaurante y eventos del hotel-laboratorio “el higuerón” de la Espam MFL. - Ramírez Rodríguez, Cristhian Eugenio (2015)
Develop a computer web system to automate the registration, lodging, restaurant and events in the tourism area management of the Hotel-Lab "El Higuerón" in the Polytechnic Agricultural University Manuel Felix Lopez at Bolivar - Manabi. It was stated the overall goal to comply with this work. For this purpose it was necessary to follow a set of specifications in order to achieve that objective. To develop the research the MIDAS methodology was used, proposing various iterations. The first iteration, MIDAS/SD requirements and the system architecture using the comprehensive collection of information. The second iteration, MIDAS/HT prototype system, where the information is classified and processes as required for the detailed design of interfaces. The third iteration, MIDAS/DB database was designed using SQL Server 2012 Express tool where the identification of the requirements collected at the stage of system being used. In the fourth iteration, MIDAS/FC was implemented dynamic functionality using the programming language C# linked to the ASP.NET technology. The hosting provided by the Data Center of the Computing Science school where the web application with their respective DB is housed; in the last iteration MIDAS/TST various system tests were conducted. Finally a system that allows the registration and control processes in the Hotel-Lab, reports to the system can be accessed reliably and securely.